2015
DOI: 10.1016/j.pcl.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome and the Development of Food Allergy and Allergic Disease

Abstract: The prevalence of food allergy and other allergic diseases continues to rise within the industrialized world, yet the cause of this epidemic remains elusive. Environmental factors such as microbial exposures have more recently been implicated as one possible driving factor behind the increasing burden of allergic disease. The impact of gut microbiome on human development, nutritional needs, and disease has become evident with advances in our ability to study these complex communities of microorganisms, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 125 publications
1
44
0
3
Order By: Relevance
“…Since food allergy is a public health problem in humans, with a prevalence of between 5 and 8%, adjuvants able to break oral tolerance are probably quite abundant. Allergies have been associated with altered diversity and composition of gut microbiota [2-4, 8], and we hypothesize that effects by adjuvants on the microbiota composition are one of their mode of action. In the present model we used CT, a commonly used adjuvant in animal studies of food allergy [24], serving as a model adjuvant, since oral exposure to the allergen alone does not induce food allergy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since food allergy is a public health problem in humans, with a prevalence of between 5 and 8%, adjuvants able to break oral tolerance are probably quite abundant. Allergies have been associated with altered diversity and composition of gut microbiota [2-4, 8], and we hypothesize that effects by adjuvants on the microbiota composition are one of their mode of action. In the present model we used CT, a commonly used adjuvant in animal studies of food allergy [24], serving as a model adjuvant, since oral exposure to the allergen alone does not induce food allergy.…”
Section: Discussionmentioning
confidence: 99%
“…Both reduced diversity and specific composition of the gut microbiome have been reported to be associated with the development of asthma, allergic rhinitis, and eczema in humans and in animal models [2-7]. Although less studied, the microbiome is also suggested to play a role in the development of food allergy [8-16]. …”
Section: Introductionmentioning
confidence: 99%
“…7375 Epidemiologic studies examining the effect of prenatal exposures on the development of allergic disease have shown that maternal exposure to farming environments during pregnancy is associated with decreased rates of AD, AR and asthma in their children. 76 Early exposure to endotoxin, a bacterial cell wall component, appears to offer protection against allergic sensitization and asthma. 77 Several reports have demonstrated a modifying effect of a SNP in the promoter region of the microbial sensor CD14 on the relationship between endotoxin exposure and atopy.…”
Section: Gene-environment Interactions In Atopic Disordersmentioning
confidence: 99%
“…The gut microbiota is considered a crucial environmental factor playing a key role in regulating the severity of allergic diseases [141]. Reduced gut microbial diversity has been reported to increase the risk of allergy in school children and in most of the cases, it is food allergy [142]. A recent study has shown that depletion of bacteria like Bifidobacterium, Akkermansia, and Faecalibacterium, along with an abundance of fungi such as Candida and Rhodotorula in neonates, may predispose to allergic susceptibility by influencing T-cell differentiation [47].…”
Section: Allergiesmentioning
confidence: 99%